The Effect Of Contact Time Variations On The Efficiency Value And The Adsorption Kinetic Mechanism Of Iron (Fe) On Batik Waste Cual Using Chitosan - Kurniawan, Widodo Budi; Aldila, Herman; Livia, Livia (Jurusan Fisika, Universitas Bangka Belitung, 2022)
English